2010
DOI: 10.1042/cbi20090427
|View full text |Cite
|
Sign up to set email alerts
|

In vivo uptake of a haem analogue Zn protoporphyrin IX by the human malaria parasite P. falciparum‐infected red blood cells

Abstract: The cellular traffic of haem during the development of the human malaria parasite Plasmodium falciparum, through the stages R (ring), T (trophozoite) and S (schizonts), was investigated within RBC (red blood cells). When Plasmodium cultures were incubated with a fluorescent haem analogue, ZnPPIX (Zn protoporphyrin IX) the probe was seen at the cytoplasm (R stage), and the vesicle-like structure distribution pattern was more evident at T and S stages. The temporal sequence of ZnPPIX uptake by P. falciparum-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…Plotting the observed absorbance increase at 415 nm as a function of PfHO concentration and fitting with a quadratic binding equation gives an apparent dissociation constant ( K d ) of 9 μ m (Fig. 6 D ), indicating modest affinity and consistent with prior reports (22, 23). A nearly identical heme affinity was determined by measuring quenching of PfHO tryptophan fluorescence upon heme binding (Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Plotting the observed absorbance increase at 415 nm as a function of PfHO concentration and fitting with a quadratic binding equation gives an apparent dissociation constant ( K d ) of 9 μ m (Fig. 6 D ), indicating modest affinity and consistent with prior reports (22, 23). A nearly identical heme affinity was determined by measuring quenching of PfHO tryptophan fluorescence upon heme binding (Fig.…”
Section: Resultssupporting
confidence: 87%
“…On the basis of in vitro assays performed with the recombinant HO-like domain of PfHO and recombinant P. falciparum ferredoxin, it was proposed that PfHO catalyzes the degradation of heme to bilirubin (22). A subsequent study of recombinant full-length PfHO (amino acids 1–305) by a different group concluded that PfHO catalyzes degradation of heme to biliverdin (23). To evaluate whether PfHO is indeed a heme-degrading enzyme, we first analyzed its sequence features and then tested the ability of recombinant PfHO to bind and degrade heme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies indicated that iron might be released during degradation of hematin by hydrogen peroxide in the digestive vacuole or by reaction with reduced glutathione in the parasite cytoplasm (see review by Scholl et al [8]). A putative heme oxygenase was recently identified in the parasite [20,21]; however, no heme oxygenase activity has been detected in infected RBCs and the designation of these enzymes as heme oxygenases has been questioned [22].…”
Section: The Art Activator: What Is It and Where Does It Come From?mentioning
confidence: 98%
“…(Sherman et al, 1965). A via alternativa de detoxificação da hemina formando BV e BR catalisada pela PfHO foi proposta pelo Okada (2009), entretanto a PfHO apresenta uma baixa ativida em converter hemina em BR (Sartorello et al, 2010) sugerindo uma função alternativa da detoxificação da hemina.…”
Section: Efeito Da Hemina Protoporfirina E Metaloprotoporfirinas Encunclassified